DDRE-26. INHIBITION OF PRMT5 SENSITIZES GLIOBLASTOMA MODELS TO TRAMETINIB TREATMENT. (12th November 2021) - Banasavadi, Yesh; Namagiri, Sriya; Otani, yoshihiro; Thammegowda, Shilpa; Sur, Hannah; Rivas, Sarah; Bryant, Jean-Paul; Chowdhury, Ashis; Lewis, Cole; Shimizu, Toshihiko; Walbridge, Stuart; Lee, Tae Jin; et al.
Abstract: With limited effective therapeutic strategies, the prognosis for glioblastoma (GBM) is very poor. Our previous study shows that the expression of Protein Arginine Methyltransferase 5 (PRMT5) is upregulated in GBM; its inhibition promotes apoptosis and senescence in differentiated and stem-like tumor cells, respectively. MEK inhibitors, including trametinib, are currently under investigation for GBM therapy. In this study, we tested whether inhibition of PRMT5 can enhance the anti-GBM efficacy of trametinib. Patient-derived primary GBM neurospheres (GBMNS) with transient PRMT5 knockdown were treated with trametinib and cell viability, proliferation, cell cycle progression, ELISA, and western blot analysis were conducted. In vivo, PRMT5-intact and -depleted GBMNS were intracranially implanted in NSG mice and treated with trametinib by daily oral gavage, and tumor progression and mice survival rate were analyzed by MRI and Kaplan-Meier survival curve, respectively. Depletion of PRMT5 increased the cytotoxic effect of trametinib in GBMNS. Trametinib treatment increased the activity of ERBB3 and AKT; With PRMT5 knockdown, the activity of both AKT and ERBB3 decreased significantly. But, inhibition of ERBB3 alone failed to block the trametinib-induced AKT activity suggesting that even though PRMT5 regulates the activity of both ERBB3 and AKT, the enhanced antitumor effect imparted by PRMT5 knockdown in trametinib treated GBMNS is because of AKT inhibition alone. In vivo, PRMT5-depletion extended the survival of the tumor-bearing mice that further increased in combination with trametinib treatment. Interestingly, trametinib treatment alone had no survival benefit.